2022
DOI: 10.1037/xge0001232
|View full text |Cite
|
Sign up to set email alerts
|

Making rights from wrongs: The crucial role of beliefs and justifications for the expression of aversive personality.

Abstract: Whereas research focusing on stable dispositions has long attributed ethically and socially aversive behavior to an array of aversive (or "dark") traits, other approaches from social-cognitive psychology and behavioral economics have emphasized the crucial role of social norms and situational justifications that allow individuals to uphold a positive self-image despite their harmful actions. We bridge these research traditions by focusing on the common core of aversive traits (the dark factor of personality [D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 121 publications
(174 reference statements)
3
19
0
Order By: Relevance
“…Also, the stronger relation of the primarily behavioral antagonistic traits, and thus behavior related to exploitation of others, with HH over BF-AG is in agreement with studies revealing HH as a stronger predictor of prosociality and (non-) exploitation than BF-AG (for a recent meta-analysis, see Thielmann et al, 2020). Furthermore, the present results indicating D to be most strongly related to the cognitive traits aligns with recent findings showing that D is a superior predictor (over and above BF-AG or HH) of justifying beliefs for socially aversive behavior (Hilbig, Moshagen, Thielmann, et al, 2022;Horsten et al, 2021;Moshagen, Zettler, Horsten, et al, 2020). Finally, the incremental effects of D over and above BF-AG in deceitfulness and manipulation (i.e., dishonesty and cheating) and the incremental effects of D over and above HH in hostility and callousness (i.e., aggression and insensitivity) are in line with prior findings .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, the stronger relation of the primarily behavioral antagonistic traits, and thus behavior related to exploitation of others, with HH over BF-AG is in agreement with studies revealing HH as a stronger predictor of prosociality and (non-) exploitation than BF-AG (for a recent meta-analysis, see Thielmann et al, 2020). Furthermore, the present results indicating D to be most strongly related to the cognitive traits aligns with recent findings showing that D is a superior predictor (over and above BF-AG or HH) of justifying beliefs for socially aversive behavior (Hilbig, Moshagen, Thielmann, et al, 2022;Horsten et al, 2021;Moshagen, Zettler, Horsten, et al, 2020). Finally, the incremental effects of D over and above BF-AG in deceitfulness and manipulation (i.e., dishonesty and cheating) and the incremental effects of D over and above HH in hostility and callousness (i.e., aggression and insensitivity) are in line with prior findings .…”
Section: Discussionsupporting
confidence: 92%
“…By comparison, BF‐AG only peripherally reflects modesty (vs. grandiosity) and trust (vs. suspiciousness), and HH only captures beliefs of superiority or entitlement (grandiosity), without any direct reference to trust versus suspiciousness. Correspondingly, it has been shown that D is strongly associated with several (classes of) justifying beliefs and predicts incremental variance over and above BF‐AG and HH (and even the entire HEXACO space) in distrust and hierarchy‐related beliefs in particular (Hilbig, Moshagen, Thielmann, et al., 2022; Horsten et al., 2021; Moshagen et al., 2018, 2020). Moreover, D predicted incremental variance beyond the HEXACO space in instances of aversive psychopathology that are primarily related to beliefs, especially narcissism (for which believing in one's superiority is integral) and paranoia (for which suspicion toward others is integral; Hilbig, Thielmann, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the disutility of others may include all forms of material, physical, or psychological costs. Justifying beliefs may rely on both implicit and explicit processes, for instance, a sense of entitlement or the belief that selfish behavior is necessary to get ahead (Hilbig et al, 2022). In analogy to the g-factor of intelligence, D is conceptualized as the basic, fluid disposition from which all aversive traits arise as specific manifestations.…”
Section: The Dark Factor Of Personalitymentioning
confidence: 99%
“…Evidence for the conceptualization of D and its predictive validity for relevant outcomes has been provided by several studies (e.g., Bader et al, 2021; Hilbig et al, 2022; Hilbig, Thielmann, et al, 2021; Moshagen et al, 2018; Moshagen, Zettler, & Hilbig, 2020; Schermer & Jones, 2020). Furthermore, the notion that aversive traits represent specific manifestations of D was supported by a four‐year study showing that D longitudinally predicted individual differences and changes in aversive traits, with strong evidence for the fluid nature of D (Zettler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, their common core, the so-called dark factor of personality (D), has been defined as “the tendency to maximize one’s individual utility—disregarding, accepting, or malevolently provoking disutility for others—accompanied by beliefs that serve as justifications” (Moshagen et al, 2018, p. 657). In line with this definition, D predicts diverse behaviors that involve utility maximization at others’ expense (Bader et al, in press; Moshagen et al, 2018; Moshagen, Zettler, Horsten, & Hilbig, 2020) and beliefs that can serve to justify such behaviors (Hilbig et al, in press; Horsten et al, 2021; Moshagen, Zettler, & Hilbig, 2020).…”
mentioning
confidence: 98%